KONTEN MATEMATIKA SEKOLAH DASAR PADA ALAT DAN PROSES PEMBUATAN KAIN TENUN MASYARAKAT KEDANG DI PULAU LEMBATA - Irene Kunang; Gregorius Sebo Bito; Marselina Wali (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
This study aims to determine the ethnomathematics in the process of making Kedang woven fabrics. The approach used is qualitative ethnographic research. The subjects in this study consisted of two Kedang weavers. The data collection process used observation, interview, and documentation techniques. Data were analyzed descriptively qualitatively. The results showed that there are mathematical concepts that can be observed in the process of making Kedang woven fabrics, namely integers, geometric concepts namely points, angles, lines, rectangles, and blocks, truncated cones and spheres. Thus the process of weaving Kedang woven cloth can be used as the content and context of elementary school mathematics learning.